ELECTRONIC MONITORING ON BEHAVIORAL PATTERNS OF DAIRY COWS IN A COOLING FREE STALL - Matarazzo, Soraia V.; Silva, Iran J. O.; Perissinoto, Maurício; Fernandes, Sérgio A.; Moura, Daniella J.; Arcaro Júnior, Irineu; Arcaro, Juliana R. P. (Revista Brasileira de Engenharia de Biossistemas, 2007)
This research aimed to use electronic monitoring for evaluating behavior patterns oflactating cows in a cooling free stall. Four video cameras were strategically installed ineach treatment for capturing in real time images of animal displac ements and activities,as intake, rumination and resting. The trial was carried out during 28 consecutive days of November 2003, in which images were daily recorded from 9 a.m. to 5 p.m. during 7days. Fifteen multiparous lactating cows producing 20 kg of milk per day were used. The tested treatments were: non-fan (F0), fan (F) and fan plus misting (FM) in direction to animal bedding. Dry bulb temperature (DBT) and air relative humidity (RH) inside and outside of facility were measured every 15 minutes during 24 hours. The RH was higher in non-fan (61.8%) and fan plus misting (61.8%) treatments than in fan (60.3%) treatment. Also, the temperature and humidity index was higher in fan (75.0) treatment than in non-fan (74.5) and fan plus misting (74.3) treatments. In the treatment with fan, animals spent more time in the feeding area (108.3 min) than those of non-fan (60.7 min) and fan plus misting (72.5 min) treatments. Fan treatment cows spent more time (19.3 min) in waterers in relation to non-fan (8.3 min). Different patterns were observed in the cow’s preference relative to resting area. The resting areas include the bedding adjacent to feeding area and bedding adjacent to waterers. Cows of non-fan (189.0 min) and fan(167.3 min) spent more time lying in the bedding adjacent to feeding area. However, the cows of treatment fan plus misting (164.0 min of total) spent more time lying in the bedding adjacent to waterers in relation fan (26.7 min). The cows of fan plus misting treatment also spent more time (35.0 min) standing in passage area (drinkers) than of non-fan and fan (10.0 min). In the current experiment, the results indicate difference infree stall occupancy. The cow’s preference was always related to the availability of cooling system.